2013
DOI: 10.1371/journal.pone.0054699
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Organization of the Yeast Genome Correlates with Co-Expression and Reflects Functional Relations between Genes

Abstract: The spatial organization of eukaryotic genomes is thought to play an important role in regulating gene expression. The recent advances in experimental methods including chromatin capture techniques, as well as the large amounts of accumulated gene expression data allow studying the relationship between spatial organization of the genome and co-expression of protein-coding genes. To analyse this genome-wide relationship at a single gene resolution, we combined the interchromosomal DNA contacts in the yeast geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…First, the interaction between the GAL1 reporters was only detected under the activating condition. This observation is consistent with previous statistical analysis, indicating that coregulated genes tend to cluster, and genes that are physically proximal tend to coexpress (21,31,32). Coactivated genes can also form "transcription factories" or "multigene complexes" in higher eukaryotic species (33,34), so our findings here are likely to be one example of a more general phenomenon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, the interaction between the GAL1 reporters was only detected under the activating condition. This observation is consistent with previous statistical analysis, indicating that coregulated genes tend to cluster, and genes that are physically proximal tend to coexpress (21,31,32). Coactivated genes can also form "transcription factories" or "multigene complexes" in higher eukaryotic species (33,34), so our findings here are likely to be one example of a more general phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…According to a statistical analysis of the Hi-C data, the Gal4 binding sites (GAL1 activator) cluster in the nucleus (21). β-estradiol-induced GAL1pr on two different chromosomes could form trans interactions under the activating condition in haploid yeast (22).…”
mentioning
confidence: 99%
“…Compartmentalization of the nucleus, chromatin loops, and longrange interactions contribute to a complex regulatory network (Lieberman-Aiden et al 2009;Kalhor et al 2011;Dixon et al 2012;Homouz and Kudlicki 2013). In P. falciparum, little is known about the effect of genome organization on gene expression.…”
mentioning
confidence: 99%
“…Moreover, recently a correlation has been suggested between transcription factor network models and distances between average chromosome positions in human cells 19 . A series of studies further reported the co-localization of each of the following groups in SC: cohesin binding sites 20 , co-expressed genes, some identified GO terms 21 and gene targets of the same transcription factor 22 . Recently, an analysis of the genomic organization of the unique P. falciparum parasite throughout its cell cycle confirmed a relation between chromosome conformation and gene expression 18 .…”
mentioning
confidence: 99%